2022
DOI: 10.21608/ejnsr.2022.247077
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between the Burden of Caregiving, Submissive Behaviors, and Depressive Symptoms Among Caregivers of Psychiatric Patients

Abstract: Background:In providing care for psychiatric patients, caregivers play a critical role. Increased caregiver's burden may increase their susceptibility to mental disorders and demonstrate submissive behavioral patterns, which are one of the least efficient coping strategies and may have a mediating effect on future depression. Aim: A study designed for exploring the relation between the burden of caregiving, submissive behaviors, and depressive symptoms among caregivers of psychiatric patients. Subjects and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A study done at Assiut University Hospital showed most study caregivers of psychiatric patients (92.5%) suffered from moderate to severe 62.6% while severe burden equivalent to 29.9% (9). Another study done at Port Said Mental Health Hospital estimated that 83.1% of psychiatric patients' caregivers have a severe level of burden and effect on their psychological well-being (10).…”
Section: Signi Cance Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…A study done at Assiut University Hospital showed most study caregivers of psychiatric patients (92.5%) suffered from moderate to severe 62.6% while severe burden equivalent to 29.9% (9). Another study done at Port Said Mental Health Hospital estimated that 83.1% of psychiatric patients' caregivers have a severe level of burden and effect on their psychological well-being (10).…”
Section: Signi Cance Of the Studymentioning
confidence: 99%
“…The positive thinking scale was developed by (13) in the Arabic language to assess individual positive thinking. It consists of 30 items and is divided into ve subscales each subscale includes six items as follows: The rst subscale is optimism and general satisfaction (1-6), the second subscale is emotional control and emotional intelligence (7)(8)(9)(10)(11)(12), the third subscale is acceptance of the others and take responsibility (13)(14)(15)(16)(17)(18), the fourth subscale is forgiveness and self-acceptance (19)(20)(21)(22)(23)(24), nally the ve subscale is a love of learning and taking risks (25)(26)(27)(28)(29)(30).…”
Section: Tools For Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations